Cultural Competence in Healthcare and Healthcare Education - Constantinou, Costas S; Andreou, Panayiota; Nikitara, Monica; Papageorgiou, Alexia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cultural competence has been acknowledged as an important set of skills and mindset for working effectively with diverse patients and for reducing social disparities in healthcare. In this Special Issue cultural competence was approached as an umbrella term and submissions relating to the whole spectrum of the concept were invited. Nine papers are published, 7 of which are research articles, 1 is a concept paper and 1 is a review, from authors from Spain, the UK, Germany, Denmark, Cyprus, France, Portugal, and Brazil. These 9 articles discuss a variety of concepts and aspects of cultural competence, such as cultural communication, cultural humility, diversity competence, and structural competence, and highlight the importance of cultural competence in healthcare and healthcare education, while opening new directions in research and policy making.